RELATIONSHIP BETWEEN FEEDING PATTERNS AND THE INCIDENCE OF STUNTING IN TODDLERS IN THE WORK AREA OF THE COMMUNITY HEALTH CENTER OF SUMOBITO, JOMBANG - Aziz, Aditya Nuraminudin; Rustanti, Elly; Ufaidah, Puput (Literasi Kesehatan Husada: Jurnal Informasi Ilmu Kesehatan, 2024)
Background: Stunting is a condition where the index of body length compared to age (PB/U) or height compared to age (TB/U) is shorter than age. Simply put, stunting is a term for growth disorders in children. Objectives: This study aimed to determine and analyze the relationship between feeding patterns and the incidence of stunting in toddlers in the Sumobito Community Health Center working area. Design: This research method uses correlational analytics with a cross-sectional approach. The research population was 209 people. The research sample consisted of 41 respondents using random sampling techniques with data collection using questionnaires on the variables of feeding patterns and height observation. Statistical analysis in this study used the Spearman Rank correlation test. Results: The research, results showed that the majority of respondents had appropriate feeding patterns, 21 respondents (51.2%), and the majority of respondents with very short stunting, 21 respondents (51.2%). Analysis of feeding patterns on the incidence of stunting showed a p-value of 0.002 < (0.05), which means that there is a relationship between feeding patterns and the incidence of toddlers in the Sumobito Jombang health center working area. Conclusion: Proper feeding patterns carried out by mothers can influence the nutritional status of toddlers if nutritional status is met, toddlers will avoid stunting.